Бриллиант Фортуны - Вербинина Валерия (Его величество случай, 2014)
Экземпляры: Узинская библиотека (20170208) / Инвентарный номер: 204067 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: В 31 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6